the Robert Wood Johnson Foundation anthology. (San Francisco, 2005)
"RWJ-sponsored projects have thoroughly examined many important issues in healthcare during the 1990s. The scholars writing each chapter are thoughtful and erudite. Reders interested in the history and programs of RWJ will certainly find the book highly informative...individual chapters in this book are gems and the dedicated reader will certainly be rewarded." — Eugene C. Rich, MD, Creighton University Medical Center, (Internet review-Doody's Weekly E-Mail Bulletin)
Keywords: Public health,Foundations,Delivery of Health Care,Y tế công cộng,Tổ chức,Cung cấp các dịch vụ chăm sóc y tế; Endowments,Sự hiến tặng; United States,United States,United States,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ